The virtues of strangers? Policing gender violence in Pacific Island countries. (12th February 2019) - Bull, Melissa; George, Nicole; Curth-Bibb, Jodie
ABSTRACT: This article considers the gap between reformist policy and practice in the policing of gender violence in Pacific Island Countries (PICs) with a key focus on Solomon Islands, Fiji and Kiribati. In doing so, we critically engage with two pervasive arguments in policing scholarship: (1) arguments regarding the value of hybridity and regulatory pluralism in PICs; and (2) the dominant critique of 'policing by strangers'. We outline and acknowledge the compelling logics of these arguments, but we contend that they are called into question when (re)evaluated through a gender lens. Drawing on in-country fieldwork observations, relevant reports from government and non-government sources, and secondary literature, we begin to map out the empirical evidence that demonstrates the fragility of such positions in the case of policing gender violence. We go on to explore the complexity of institutional reform processes in PIC police forces by providing an overview of the intersection between informal operating cultures and police reform agendas – particularly as they relate to the policing of gender violence. We argue that Georg Simmel's (1950) idea of the stranger, illustrating the contradictory experience of what it means to engage with someone who is spatially close but socially distant, offers a framework for exploring policing reform in the context of gender violence. Approaching gender violence through the lens of the 'stranger' potentially supports the development of a context-specific professional ethic that is able to effectively navigate conflicting forms of authority that currently undermine policing in PICs to provide better outcomes for women.